Exploring the facilitation of young children with disabilities in research about their early intervention service. (October 2016) - Carroll, Clare; Sixsmith, Jane
While participatory research approaches are being developed and applied within speech and language therapy practice it is not clear that all children are afforded the opportunity to participate in such activities. This study aimed to explore the involvement of young children, aged between two and four years, with developmental disabilities in the research process, focusing on early intervention disability services. Eight young children took part in this qualitative research. Clark and Moss's (2011) framework for listening was used to structure the multi-method data collection process. The design was iterative; the collection of data from each participant was followed by a review of theoretical ideas to support the emerging data. Findings suggest that the use of an asset based approach to participation in research, focusing on participants strengths through a variety of data collection tools, used by a skilled facilitator, supported by parental expertise enabled the children to be part of the data collection process. The research highlights that speech and language therapists can facilitate the inclusion of children with disabilities in research activities about their early intervention service they receive. As members of early intervention teams speech and language therapists need to promote their skills in facilitating the active engagement of children with developmental disabilities in research. Thus making their participation in early intervention research, a reality with potential to promote holistic practice.